HUBUNGAN POLA TATA RUANG DENGAN ASPEK BIOKLIMATIK PADA PERPUSTAKAAN UMUM - 'Afifah Nurul Hidayah; Afif Fajar Z (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2024)
Library is a place that is a center of information and reference for visitors. The library also plays a role as a supporter of efforts to educate the nation. However, the culture of visiting the library is currently declining, many people tend to spend their free time going to shopping centers rather than adding insight at the library. This may be due to by the lack of facilities in the library and spatial patterns that cannot provide a comfortable atmosphere for visitors to live in longer. In an effort to attract visitors, the library must be able to provide better access to its resources, users, and services, as well as provide complete and comfortable facilities for both children and adults. The application of bioclimatic architecture that examines the relationship between humans, building design, and the surrounding climatic conditions can be used as a reference in building design to meet comfort and energy savings. This research will examine more deeply the relationship between spatial patterns and bioclimatic aspects in public libraries, by taking samples based on literature studies at the Warrnambool Learning and Library Center and the UM Library. The research is presented using a qualitative descriptive method by concluding that the bioclimatic aspect will affect the arrangement of spatial patterns in public libraries, so as to provide comfort to its users.